PERANCANGAN SISTEM INFORMASI BUKU TAMU PADA KANTOR CAMAT KOTA KISARAN TIMUR - Revo Ardhana (CV Edujavare Publishing, 2024)
The development of information technology has encouraged various government agencies to transform in utilizing digital systems to provide services to the public. One of them is the East Kisaran City Subdistrict Office which needs a system to make it easier to manage guest data. This report proposes designing a digital guestbook application which aims to replace the manual guestbook system currently used. This application is designed to record visitor data in an efficient and structured manner, and allows for automatic recording of visit times, requirements and guest identities. By using this application, it is hoped that the guest administration process can be carried out more quickly, accurately and easily accessed. The design of this application involves needs analysis, interface design, and implementation of a web-based system that can be accessed by officers at the sub-district office. The results of this research show that the digital guestbook application can increase efficiency in managing visitor data and reduce the potential for errors in recording data.